Using standards to improve teaching and learning - Creed, Bill; Steinhorn, Pauline; Association for Supervision and Curriculum Development (Alexandria, Virginia : Association for Supervision and Curriculum Development, 2000)
This program formulate the using of standards in improving roles and school structure, curriculum and assessment and also improving classroom instruction
Executive producer, John Creckley ; editors, Judy Herbert, Laurel Cobble and Bill Creed
Keywords: Teacher participation in curriculum planning; Classroom management; Educational tests and measurements